AgNps-PVA–coated woven cotton fabric: Preparation, water repellency, shielding properties and antibacterial activity. (June 2019) - Xu, Jiangtao; Jiang, SX; Peng, Linghui; Wang, Yuxiang; Shang, Songmin; Miao, Dagang; Guo, Ronghui
Nowadays, there is a large demand for smart textiles by consumers. Smart textiles have different functions, and can provide comfort, safety and protection. In this study, electro-conductive woven cotton fabric is prepared in two steps. The cotton fabric samples are first impregnated and padded with a polyvinyl alcohol solution of 5% for multiple cycles (1, 3, 5 and 7 cycles) and dried. Then, silver nanoparticles are deposited onto the fabric through magnetron sputtering technology. The coated samples are examined using a Fourier transform infrared spectrometer, scanning electron microscope and X-ray diffractometer. The ultraviolet blocking, infrared reflection, electromagnetic shielding, and antibacterial properties are evaluated, as well as the contact angle, light transmittance and electrical conductivity. The results show that a polyvinyl alcohol film is successfully formed and the cotton fabric fibers are stuck together through hydrogen bonds. The light transmittance is increased after the polyvinyl alcohol pretreatment. After undergoing seven cycles of coating with polyvinyl alcohol, the silver nanoparticles-coated samples show large contact angle of 127.6°, excellent ultraviolet blocking property, a high infrared reflectivity of 30%, electrical resistivity of 1.46 × 10 –6  Ω·m, electromagnetic interference shielding effectiveness of −20 dB and antibacterial efficacy of >99.5%. Compared to the untreated and silver-coated cotton without impregnation of polyvinyl alcohol, the silver nanoparticles–polyvinyl alcohol-coated cotton fabric sample has excellent performance, which makes it a promising textile with a multitude of protective properties.